2019
DOI: 10.1007/s42452-019-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun cellulose acetate and poly(vinyl chloride) nanofiber mats containing silver nanoparticles for antifungi packaging

Abstract: Nanofiber mats of poly(vinyl chloride) (PVC) and cellulose acetate (CA) encapsulated with silver (Ag) nanoparticles were fabricated via electrospinning for potential use as antimicrobial food packaging materials. 16 wt% PVC was prepared in 1:1 w/w tetrahydrofuran-N,N-dimethylformamide while 16 wt% CA was prepared in 3:2 (w/w) Acetone-N,N-dimethylformamide. Scanning electron microscopy analysis showed that thinner fibers could be electrospun from cellulose acetate as compared to poly(vinyl chloride) at the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 65 publications
(74 reference statements)
0
22
0
1
Order By: Relevance
“…From the mechanical test results, it was observed that as the amount of TTO oil increased, the strength and strain values also improved. PU nanofibers containing 5% TTO showed more significant in vitro antibacterial activity against Escherichia coli and Staphylococcus aureus than control PU nanofibers [ 161 , 162 , 163 ]. The cell counting kit-8 assay performed on NIH-3T3 cells revealed that each sample’s cell proliferation with different TTO contents was similar to the control group.…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%
“…From the mechanical test results, it was observed that as the amount of TTO oil increased, the strength and strain values also improved. PU nanofibers containing 5% TTO showed more significant in vitro antibacterial activity against Escherichia coli and Staphylococcus aureus than control PU nanofibers [ 161 , 162 , 163 ]. The cell counting kit-8 assay performed on NIH-3T3 cells revealed that each sample’s cell proliferation with different TTO contents was similar to the control group.…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%
“…To prevent fungal growth and mycotoxin production in food materials and packaging; hybrid nanofiber mats composed of cellulose acetate encapsulated with AgNPs were prepared by electrospinning. Due to close tight assembly of packaging in food materials, these nanofiber mats allowed low penetration of air permeability preventing fungal growth, and silver nanoparticles inherently inhibited the growth of yeast and molds [ 73 ]. Thus, these nanocomposite materials have shown great potential for future applications in the food packaging and preservation industry.…”
Section: Nanocomposites and Their Mode Of Action On The Fungal Phymentioning
confidence: 99%
“…The high tensile elongation is evident as well as the presence of a high modulus and a low modulus region on the plot as has been previously described for randomly aligned nanofiber mats. 29 The high modulus region indicates the breaking of adhesion points between the nanofibers upon application of tensile load while the low modulus region indicates when the nanofibers are sliding over each other after the adhesion points have all been severed.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…As such, the polymer has been electrospun successfully using some of these solvents where the properties of the nanofiber mats have been reported to be subject to type of solvent, solution properties, and process settings. [26][27][28][29] Investigations on the use of PVC nanofibers in nonwoven form have shown that they possess excellent filtration properties and reach sufficiently high filtration efficiencies. 30,31 In light of the advantages of the electrospinning process and the unique properties of electrospun nanofibers, this study aims to demonstrate the development of a PVC nanofiber composite membrane having adequate mechanical properties for particular filtration applications.…”
Section: Introductionmentioning
confidence: 99%